Constitutive model and failure locus of a polypropylene grade used in offshore intake pipes. (February 2017) - Yurindatama, D.; Barsoum, I.
Abstract: BorECO ® ™ BA212E is a polypropylene block co-polymer which has become a common material in the manufacturing of large diameter non-pressurized gravity offshore intake pipelines. These lines are used for transportation of sea water for cooling of petrochemical process plants. The pipe sections are joined by butt heat fusion welding to create the pipeline. Recently a few premature failures of such pipelines have been reported in the field. Hence, there is a need to characterize the constitutive behavior of the pipe and weld material in order to properly design these pipes. The aim of this work is to determine the material constitutive behaviors of the pipe material and the welded joint material. Uniaxial tensile tests of both the pipe and weld joint material are conducted at various strain rates. Both the pipe and weld material show a rather high strain rate dependency, with the weld material having about half the yield strength than that of the pipe material. An analytical constitutive material model is developed for both the pipe and weld material, incorporating the effect of strain rate. The failure locus, expressed in terms of the equivalent plastic strain at failure vs. the stress triaxiality, for both materials is also determined as part of the constitutive model using notched dumbbell specimens. The constitutive model and failure loci for the pipe and weld material are implemented in a finite element model (FEM) and are validated by conducting a series of independent four-point bend experiments on both material types. The validation is carried out by comparing the FEM results of the four-point bend model with the experimental results, which show a rather good agreement.